2014
DOI: 10.1186/1743-0003-11-22
|View full text |Cite
|
Sign up to set email alerts
|

The effect of arm weight support on upper limb muscle synergies during reaching movements

Abstract: Background: Compensating for the effect of gravity by providing arm-weight support (WS) is a technique often utilized in the rehabilitation of patients with neurological conditions such as stroke to facilitate the performance of arm movements during therapy. Although it has been shown that, in healthy subjects as well as in stroke survivors, the use of arm WS during the performance of reaching movements leads to a general reduction, as expected, in the level of activation of upper limb muscles, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
115
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 59 publications
25
115
1
Order By: Relevance
“…Even when only compensating for one-fourth of the gravity moment, the WPCSE promisingly reduced the average (ranging from 9% to 35%) and peak (ranging from 10% to 33%) neuromuscular activity of several muscles crossing the shoulder during positive shoulder elevation/adduction. Our results are consistent with several previous studies that also showed that varying levels of gravity compensation at the shoulder can reduce muscle activity [8,9,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Even when only compensating for one-fourth of the gravity moment, the WPCSE promisingly reduced the average (ranging from 9% to 35%) and peak (ranging from 10% to 33%) neuromuscular activity of several muscles crossing the shoulder during positive shoulder elevation/adduction. Our results are consistent with several previous studies that also showed that varying levels of gravity compensation at the shoulder can reduce muscle activity [8,9,36,37].…”
Section: Discussionsupporting
confidence: 93%
“…In order to simplify the comparison of the muscle synergies among conditions, the same number of muscle synergies was retained within the same condition across participants; the number was established as the rounded average across participants [33,38]. The NNMF algorithm does not extract muscle synergies in the same order for each subjects and different walking modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Using the robotic upper limb exoskeleton ALEx [39, 40], we designed a three-dimensional point-to-point reaching task (Fig. 1a-b), a training exercise commonly used in robotic rehabilitation therapy [41–43]. In order to challenge the subjects and make them adapt to a new motor control scheme with temporal dynamics similar to those observed in robot-aided rehabilitation of stroke patients, the visual feedback was manipulated during five inversion blocks B 1-5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using the robotic upper limb exoskeleton ALEx [39, 40], we designed a three-dimensional point-to-point reaching task, a training exercise commonly used in robotic rehabilitation therapy [41–43]. The movement amplitude was selected to allow the exploration of a functional workspace, while movement directions were chosen to elicit independent and synergistic motion of shoulder and elbow, capitalizing on the advantages provided by robotic exoskeleton devices [51].…”
Section: Discussionmentioning
confidence: 99%